FACTORS AFFECTING THE ROLE OF PEER COUNSELORS IN IMPLEMENTING ADOLESCENT REPRODUCTIVE HEALTH EDUCATION IN SUMENEP DISTRICT - Dian Permatasari; Emdat Suprayitno (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2021)
Adolescents are considered as priority targets for reproductive health that will determine the quality of reproductive health in the future. The globalization of information has a big impact on adolescents. The great curiosity of adolescents about reproduction encourages adolescents to seek information from various sources, including peers, parents, schools and information media. This requires correct and responsible information so that adolescents can have healthy reproductive behavior. This study aims to analyze the factors that influence the behavior of peer counselors in the implementation of adolescent reproductive health counseling in Sumenep Regency. P enelitian uses quantitative methods to design cross-sectional. The population in this study is the total population, namely all peer counselors who have received training on Adolescent Reproductive Health in Sumenep Regency in 2020 as many as 66 people. Data analysis used chi-square statistical test and logistic regression. The results showed that the most dominant factor influencing was knowledge of KRR counseling, motivation towards the implementation of KRR counseling, support of officers for the implementation of KRR counseling, and the supervision of officers on the implementation of KRR counseling. This study recommends the Sumenep Regency BPMP & KB Office to organize and activate adolescent reproductive health counseling training and invite peer counselors who are active in Sumenep district, and facilitate any KRR counseling activities, namely in the form of facilities and infrastructure.